Envolvimento dos sistemas dopaminérgicos e serotoninergico no efeito tipo antidepressivo causado pelo fenilselenometil-1,2,3-triazol em camundongos - Donato, Franciele (2013)
Depression is a common mental disorder associated whth a signigicant negative impact n quality of life, morbidity, and cognitive function. The monoamine theory of depression postultes that this disease results from a deficiency of brain monoaminergie activity, however other neural systems and biochemical process, like oxidative stress, appear to be involved in its pathogenesis. The aims of the study were investigated the antidepressant like effect, acute toxicity of 4-phenyl-1-(phenylselanylmenthyl)-1,2,3-trizole (Se-TZ), (an organocompounds selenium-containing heterocycles), administered by oral route, in mice. The results evidenced that administration of Se-TZ, significantly reduced immobility time in tail suspension test (TST), without altering locomotor and exploratory activity in the open-field test (OFT). The antidepressant-like effect of Se-TZ ib the TST was prevented by pretreatment of miche with SCH23390 (0,5 g/Kg, s. s, selective D1 receptor antagonist), sulpiride (50 mg/Kg, i.p., selective D2 receptor antagonist) and methysegide ( 2 mg/Kg, s.c., non-selective 5-HT receptors antagonist), but not with prazosin ( 1 mg/Kg, i.p., an α 1 –adrenoreceptor antagonist), yohimbine ( 1 mg/Kg, i.pi.; an α 2-adrenoreceptor antagonist) and propranolol (2 mg/Kg i.p.; β-adrenoreceptor antagonist). The determination of levels of monoamine neurotransmitters and their metabolites cooperating with results obtained previously in TST. In this context, the Se-TZ, increased monoamine neurotransmitters dopamine (DA) an serotonin (5-HT) levels in the cerebral cortex an hippocampus, whereas norepinephrine (NE) levels, were not altered. This study also showed that 72 hours after administration of single oral dose of Se-TZ, the paramenters of acute toxicity to biochemical makers hepatic damage: aspartate aminotransferase (AST) and alanine aminotransferase (ALT) and renal: urea and creatinine, were not altered. Furthermore, the results evidenced that exposure to Se-TZ caused a significant increase in the catalase (CAT) activity in the cerebral cortex and hippocampus, however the glutathione S-tranferase CGST) activity increased only in cerebral cortex. The lipid peroxidation and NPSH (non protein thiols) levels, were not changed. These results suggest that the Se-TZ presented antidepressant effect, mediated through the dopaminiergie (D1 and D2) and serotonergie neurotransmitter systems, without causing acute toxicity in biochemical makers of liver and kidney damage evaluated.